RISET AKUNTANSI DI INDONESIA: INTEGRATED REPORTING DAN PELAPORAN KORPORAT - Dosinta, Nina Febriana (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
Integrated reporting (IR) was once questioned because standard setters in Indonesia have not required it. Corporate reports in Indonesia are voluntarily present in the form of IR. Although the preparation of IR in Indonesia is optional, it has been anticipated by reviewing corporate reporting research. Therefore, this study investigates IR in accounting research publications in Indonesia. This research uses a systematic literature review from 2017-2022 through nineteen articles in accounting journal publications indexed by the Science and Technology Index (SINTA) 1 and 2. The results show that research on IR in Indonesia began in 2017 with the dominance of quantitative methods referring to the International Integrated Reporting Council (IIRC). IR's research in Indonesia shows the minimal use of qualitative methods exploring standard setters in Indonesia. In the 2017-2022 publication period, IR in accounting research in Indonesia was dominated by companies listed on the Indonesia Stock Exchange using agency theory and stakeholder theory.